Ordinary Vessels: Disability Narrative and Representations of Faith - Mintz, Susannah B. (Disability Studies Quarterly, 2006)
The lived experience of disability is increasingly prominent in autobiographical writing. Numerous collections of creative work attest to an expanding market for stories that challenge prevalent stereotypes associated with disability. At the same time, scholars have begun to call for the incorporation into disability studies of poststructuralist critical theory, attempting to extend our understanding of disability beyond both medical and social models. Recent work presents disability as a diverse and ever-changing set of bodies and experiences that eludes any sort of universalizing metanarrative. A further question concerns the convergence in life writing of theory and faith: how do disabled writers interrogate stable identity while also representing religious belief? With close attention to memoirs by Nancy Mairs and Stephen Kuusisto, this paper explores the articulation of "disability theology" by writers committed to challenging the forms of stigma that attach to bodies marked by the difference of disability, as well as bodies generally as they are denigrated by Christianity. Do disability/faith narratives push inevitably toward the resolution of holy reward? Does faith somehow require self-representation as triumphant consciousness, transcending physical failure? How are narratives of spiritual compensation, which tend to suggest that disability can only be endured with the promise of heavenly reparation, inherently problematic from the perspective of disability activism? Conversely, how might narratives that resist cultural pressure to subordinate anomalous bodies to the radiance of the soul or the proficiency of the mind broaden our awareness of the locations and meanings of disability?